A comprehensive review of self-powered sensors in civil infrastructure: State-of-the-art and future research trends. (1st May 2021) - Salehi, Hadi; Burgueño, Rigoberto; Chakrabartty, Shantanu; Lajnef, Nizar; Alavi, Amir H.
Highlights: A summary of recent applications of self-powered sensors in civil engineering is presented. Significance and the advantages of deploying self-powered sensors are discussed. Potential research trends for using self-powered sensors in civil infrastructures are identified. Abstract: Rapid development in structural health monitoring systems has led to the invention of various sensing technologies. Nonetheless, difficulties in deploying and maintaining traditional wired sensors and managing vast amount of data collated from a dense array of wired sensors were fundamental drawbacks of using such systems. Wireless sensor networks (WSNs) were thus introduced to overcome the noted shortcomings. However, the energy required to power WSNs has become an important concern due to battery limitations. Energy harvesting technologies have been developed to extend the lifetime of WSNs by addressing the energy constraint problem. Recently, a new generation of WSNs based on self-powered sensors have become a reality by bridging the gap between the harvested energy and the energy required for sensing, computation, storage, and communication. Self-powered sensors are increasingly being used and establishing themselves as promising solutions to conventional WSNs in civil infrastructure. This review paper summarizes the applications of self-powered sensors in civil infrastructure during the last decade. First, a general introduction to self-powered sensing and its significance in civil engineering are presented. Thereafter, various self-powered sensors currently used in civil engineering arena are reviewed. Finally, the advantages of deploying these sensors are presented, and future research trends for their innovative use are highlighted.